2021
DOI: 10.4491/ksee.2021.43.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Current Research Trends on the Effects of Microplastics in Soil Environment Using Earthworms: Mini-Review

Abstract: Objectives : The increase in the amount of plastics used has brought convenience to human life, but has also caused various environmental problems such as problems related to microplastics. Microplastics are defined as small plastic particles with a size of under 5 mm. As of now, research on microplastics has been largely focusing on the marine environment, and studies on microplastics in soil environment are on the rise in very recent years. Thus, the environmental impact of microplastics on the soil environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Recent studies reported that the effects of MPs on marine environment have been extensively studied but there are less studies on the effects of MPs on terrestrial environment, 10) thus, there needs to be more studies on the effect of MPs on terrestrial environment. 11) The impacts of MPs on marine organisms and terrestrial organisms can be different. Many studies reported adverse effects on different marine organisms including fish.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the effects of MPs on marine environment have been extensively studied but there are less studies on the effects of MPs on terrestrial environment, 10) thus, there needs to be more studies on the effect of MPs on terrestrial environment. 11) The impacts of MPs on marine organisms and terrestrial organisms can be different. Many studies reported adverse effects on different marine organisms including fish.…”
Section: Introductionmentioning
confidence: 99%
“…풍화 등의 자연 분해 과정에 의해 분해되어, 미세플라스틱(<5 mm)을 생성한다 [2]. 특히, 많은 기존 연구들이 해양 환경 중 미세플라스틱의 영향에 대해 보고하고 있고 [3,4], 미세플라스 틱에 의한 육상 환경오염에 대한 관심은 최근 크게 증가하고 있다 [5][6][7][8]. 국내에서도 농경지 토양에서 폴리에틸렌(polyethylene; PE), 폴리염화비닐(polyvinyl chloride; PVC), 폴리프 로필렌(polypropylene; PP) 등 다양한 종류의 미세플라스틱 이 검출되는 사례가 보고된 바 있다 [6].…”
unclassified